Efficacy of a Proprietary Trigonella foenum‐graecum L. De‐Husked Seed Extract in Reducing Menopausal Symptoms in Otherwise Healthy Women: A Double‐Blind, Randomized, Placebo‐Controlled Study. (14th July 2017) - Steels, E.; Steele, M.L.; Harold, M.; Coulson, S.
Abstract : Trigonella foenum‐graecum seed extract has demonstrated hormone modulatory activity, providing biological plausibility for relieving menopausal symptoms. The study aimed to assess efficacy of a standardized T. foenum‐graecum de‐husked seed extract in reducing menopausal symptoms in healthy aging women. The study was a double‐blind, randomized, placebo‐controlled trial that recruited 115 women aged 40 to 65 years of which 59 were allocated to active ( n = 54 completed) and 56 to placebo ( n = 50 completed). Active treatment was T. foenum‐graecum de‐husked seed extract, 600 mg per day for 12 weeks. Outcome measures included Menopause‐Specific Quality of Life (MENQOL) questionnaire, frequency of hot flushes and night sweats and serum estradiol levels. There was a significant reduction in menopausal symptoms in the active group compared with placebo as assessed by total MENQOL score ( p < 0.001); reflected by significant improvements in the vasomotor ( p < 0.001), psychosocial ( p < 0.001), physical ( p < 0.001) and sexual symptoms ( p < 0.001) domains. Vasomotor outcomes correlated with hot flushes, the active group reporting significantly less daytime hot flushes and night sweats at 12 weeks ( p < 0.001). The average estradiol levels were similar in both the active group and placebo group after treatment. This study demonstrated that this proprietary T. foenum‐graecum de‐husked seed extract may reduce menopausal symptoms in healthy women. Copyright © 2017 John Wiley & Sons, Ltd.